2019
DOI: 10.1073/pnas.1810388116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture and adaptations of Nunavik Inuit

Abstract: The Canadian Inuit have a distinct population background that may entail particular implications for the health of its individuals. However, the number of genetic studies examining this Inuit population is limited, and much remains to be discovered in regard to its genetic characteristics. In this study, we generated whole-exome sequences and genomewide genotypes for 170 Nunavik Inuit, a small and isolated founder population of Canadian Arctic indigenous people. Our study revealed the genetic background of Nun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…The central High Arctic (LeMoine et al 2003), Somerset Island (Damkjar 2000), western Victoria Island (Savelle et al 2012), Foxe Basin (Savelle and Dyke 2014), and northern Labrador (Desrosiers 2017; Renouf 2003) have also produced isolated dates that may point to Late Dorset populations persisting into the thirteenth century or later. The situation in Nunavik (northern Quebec) is currently unresolved, but it is also a good candidate for Late Dorset occupations with the potential for overlap with Thule (Labrèche 2015; Pinard and Gendron 2009; Plumet 1979, 1989), particularly given a new genetic analysis that may indicate some gene flow between Paleo-Inuit and Inuit in the region (Zhou et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central High Arctic (LeMoine et al 2003), Somerset Island (Damkjar 2000), western Victoria Island (Savelle et al 2012), Foxe Basin (Savelle and Dyke 2014), and northern Labrador (Desrosiers 2017; Renouf 2003) have also produced isolated dates that may point to Late Dorset populations persisting into the thirteenth century or later. The situation in Nunavik (northern Quebec) is currently unresolved, but it is also a good candidate for Late Dorset occupations with the potential for overlap with Thule (Labrèche 2015; Pinard and Gendron 2009; Plumet 1979, 1989), particularly given a new genetic analysis that may indicate some gene flow between Paleo-Inuit and Inuit in the region (Zhou et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, longer periods of relatively close interaction would be expected to be visible in evidence for gene flow between the populations. Most recent analyses, however, indicate no substantial contribution of Dorset to the DNA of Thule or more recent Inuit populations (Raghavan et al 2014; cf., Zhou et al 2019). Given our complete lack of thirteenth- or fourteenth-century Dorset skeletal remains, we are unable to assess whether Thule interaction left a genetic trace in Late Dorset.…”
Section: The Dorset-thule Succession: Categories Of Evidencementioning
confidence: 99%
“…Understanding the ‘push’ and ‘pull’ influence of environment on the migration and sustainability of peoples in northern North America over the last millennia is arguably one of the most important elements of understanding how recent climate change may affect society and lead to genetic adaptations 1 , 2 . The timing of migration has often been associated with paleo- temperature reconstructions that link evidence of distinctive material culture 3 as well as the impact of subsistence practices in areas where hunting camps were established 4 with shifting conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Whole exome sequencing, which documents the variation in protein-coding sequences, has also been used as a tool to investigate natural selection. A number of studies in isolated populations have identified genetic variation that confers protection against environmental conditions such as adaptation to hypoxia at high altitudes among Tibetans 12 or arctic climate among Nunavik Inuit 13 and Siberians 14 . Signatures of natural selection are detected even in the context of more recent population divergence and this influences many aspects of physiology, underscored by variations in genes that impact on height, blood coagulation, pigmentation, diet availability and resistance to infections 15,16 .…”
Section: Introductionmentioning
confidence: 99%